FORMATION OF POROUS SILICON ON A HIGHLY DOPED P-TYPE MONOCRYSTALLINE SILICON - A. D. Hurbo; A. V. Klimenka; V. P. Bondarenko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Porous silicon layers were formed on a p-type silicon wafers by electrochemical anodisation. Dependencies of thickness and porosity of porous silicon layers as well as effective valence of silicon dissolution versus anodizing time and current density were obtained and analysed. A mathematical model for growth of layers of porous silicon was developed.